2019
DOI: 10.1039/c9fo01209e
|View full text |Cite
|
Sign up to set email alerts
|

Formation and conversion of characteristic volatile compounds in grilled eel (Astroconger myriaster) during different processing steps

Abstract: The aroma of grilled eel is affected by three key processing steps: curing, steaming, and grilling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…2 b). The lipid degradation generates low threshold aldehydes and alcohols, such as hexanal, (E,E)-2,4-decadienal, (E)-2-nonenal, etc., which contribute to the fishy and fatty notes ( Bassam, Noleto-Dias, & Farag, 2022 ; Ferreira et al, 2016 ; Huang et al, 2019 ; Sohail et al, 2022 ). Instant green tea can inhibit lipid oxidation and reduce the content of aldehydes ( Alghazeer et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 b). The lipid degradation generates low threshold aldehydes and alcohols, such as hexanal, (E,E)-2,4-decadienal, (E)-2-nonenal, etc., which contribute to the fishy and fatty notes ( Bassam, Noleto-Dias, & Farag, 2022 ; Ferreira et al, 2016 ; Huang et al, 2019 ; Sohail et al, 2022 ). Instant green tea can inhibit lipid oxidation and reduce the content of aldehydes ( Alghazeer et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The chromaticity of colour reflected the extent to which volatile compounds and their odours affect the aroma of clam soup during heat treatment. By virtue of such odour coding, the representation of odours could be converted to intuitive vision (Huang et al ., 2019). Meanwhile, it could be used as a reference benchmark for production chain and flavour quality of heat‐treated clam soup.…”
Section: Resultsmentioning
confidence: 99%
“…GC–MS and electronic nose (E‐nose) are commonly combined with sensory evaluation results to objectively identify volatile compounds and assess odours (Chambers IV & Koppel, 2013), but the results do not allow intuitive and convenient differentiation of flavour volatiles (Weng et al ., 2021). The odour coding is an effective and practical method to convert unknown odour expression into intuitive vision (Huang et al ., 2019). Currently, studies on the link between thermal reaction temperatures and key compounds by odour coding have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wang, et al [ 28 ] examined the performance of electronic nose sensors in detecting volatile compounds in pork at different cooking times/temperatures; they found that the sensors that were in SHS (superheated steam) mode performed better than other sensors. Huang, et al [ 29 ] used an electronic nose to detect different types of volatile compounds in eels, for three modes of curing, steaming, and grilling; according to the radar diagram in their research, the fingerprints in all three modes of cooking were very similar. They also found that after cooking, the intensity of the smell of the samples intensified and the efficiency of the sensors changed.…”
Section: Discussionmentioning
confidence: 99%